2000
DOI: 10.1097/00005537-200003000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Activity Is Upregulated in Laryngeal Squamous Cell Carcinoma

Abstract: Objective/Hypothesis: The immortalizing enzyme telomerase has been linked to carcinogenesis and is being targeted as a novel molecular marker. This study investigated telomerase expression in patients with laryngeal squamous cell carcinoma and correlated telomerase activity with conventional prognostic parameters. Study Design: A consecutive series of patients with laryngeal squamous cell carcinoma undergoing surgical salvage for persistent or progressive disease after failed radiation therapy. Methods: Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…In the carcinogenesis of squamous cell carcinoma in the oral cavity, telomerase reactivation most probably represents an early event and is already detectable in a moderately dysplastic oral squamous epithelium (22). In the larynx, from 68 -100% of laryngeal squamous cell carcinomas show telomerase reactivation (11)(12)(13)(14)(15)(16)(17), although the exact role and timing of telomerase reactivation in laryngeal carcinogenesis are still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the carcinogenesis of squamous cell carcinoma in the oral cavity, telomerase reactivation most probably represents an early event and is already detectable in a moderately dysplastic oral squamous epithelium (22). In the larynx, from 68 -100% of laryngeal squamous cell carcinomas show telomerase reactivation (11)(12)(13)(14)(15)(16)(17), although the exact role and timing of telomerase reactivation in laryngeal carcinogenesis are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that hTERT mRNA may occasionally be detected in a normal laryngeal epithelium, but the frequency and relative quantity of hTERT mRNA is significantly higher in laryngeal squamous cell carcinomas (11). To the best of our knowledge, only six studies to date have been published using a telomeric repeat amplification protocol (TRAP) for the measurement of telomerase activity in the larynx and/or hypopharynx (12)(13)(14)(15)(16)(17). The main drawback of these studies is the lack of uniformly applied terminology for different grades of epithelial abnormalities, as well as imprecise methodology used for detection of telomerase activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Most laryngeal cancer cells persistently express high levels of telomerase activity, whereas a healthy laryngeal epithelium rarely displays it. 11,12 The 2 main components of telomerase are the template human telomerase RNA (TR) and a human telomerase reverse transcriptase (TERT) catalytic subunit. Studies have shown that TERT expression is likely to be the rate-limiting factor in regulating telomerase activity.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…Eighty-five percent of all cancers are telomerase positive, while for most normal somatic cells, telomerase activity is absent or very low. [4][5][6] Therefore, telomerase is considered an ideal target for cancer therapy, and many strategies have been developed to inhibit telomerase, such as antisense nucleotides, ribozymes, dominant-negative proteins, and small synthetic molecules. 7,8 RNA interference (RNAi) represents an evolutionarily cellular mechanism for controlling expression of genes in almost all eukaryotes, including humans.…”
Section: Introductionmentioning
confidence: 99%